Review of Mathematical Models of Vaccination for Preventing Congenital Cytomegalovirus Infection - Lanzieri, Tatiana M (J Infect Dis, 2020)
BACKGROUND: Several cytomegalovirus (CMV) vaccine candidates are under development. To reduce the burden of congenital CMV infection, potential strategies under consideration include vaccination of adult women, adolescent girls, and/or young children (both sexes). METHODS: We reviewed 5 studies that used infectious disease modeling to assess the potential impact of vaccination for preventing congenital CMV infection. All models assumed CMV vaccination would prevent primary infection and 2 models also assumed prevention of reinfections and reactivations. RESULTS: Despite differences in structure, assumptions, and population data, infant vaccination (both sexes) was the optimal strategy in all models, but in 1 model vaccinating seronegative women at 19–21 years of age was also optimal (for duration of vaccine protection ≥8 years). In 3 models, infant vaccination increased average age at primary infection as a result of decreased secondary transmission (herd immunity) combined with waning vaccine-induced immunity. This effect could increase the risk of congenital CMV infections in populations where primary CMV infection occurs early in childhood but could be minimized by administering a second dose of vaccine during adolescence. CONCLUSIONS: Understanding vaccine efficacy and duration of immunity, and how these might vary depending on CMV serostatus and age at vaccination, will be key to defining CMV vaccination strategies.